Middle East and North African Health Informatics Association (MENAHIA): A New Opportunity for the Region - Alshammari, Riyad; Al-Shorbaji, Najeeb; Ahmed, Zakiuddin; Al-Hamadan, Zaid; Alshammari, Abdulwahhab; El Hassan, Osama; Alhuwail, Dari; Al Salmi, Salim; Al-Jafar, Eiman; Ghazal, Hassan (Yearbook of Medical Informatics, 2019)
During the 2018 IMIA General Assembly (GA) held on Oct 2018 in Sri Lanka, a new organization, the Middle East and North African Health Informatics Association (MENAHIA) was established as a regional non-governmental organization to promote Health Informatics in the region. Health Informatics activities in applications, education, and research have been growing in the Middle East and North African region for many years. Over the past year, health informatics initiatives within the region focused on the education sector and the workforce. The need to enhance the education delivery and methods is essential in promoting Health Informatics in the region as well as establishing master programs in many countries within the region.This paper provides an overview of the variety of initiatives that are occurring in the region and are endorsed by MENAHIA.
Keywords: Saudi Arabia; Pakistan; Jordan; United Arab Emirates; Morocco; Kuwait; Oman; Bahrain; Health Informatics; the Middle East